HUBUNGAN KECERDASAN SPIRITUAL DALAM PERILAKU VERBAL ABUSE PADA MAHASISWA BIMBINGAN DAN KONSELING - Deliati Deliati; Asbi Asbi; Elfrianto Elfrianto (Universitas Islam Negeri Sumatera Utara Medan, 2023)
Spiritual intelligence functions to integrate emotional intelligence and intellectual intelligence which is a potential that exists within humans. Thus, individuals have a high moral value. Spiritual intelligence is able to move a person (red. student) to become a better human being by not only being qualified in religious knowledge but also qualified in social acts of piety [1]. Students who have spiritual intelligence are able to maintain harmony, harmony in their daily lives and be humane towards others [2]. One indicator of students who are spiritually healthy is having an attitude of social responsibility, showing a sense of concern for others, having the attitude and potential to want to help when they see other people's difficulties, viewing life realistically, and gaining spiritual significance through a prosocial attitude. This research uses a qualitative approach in the library research method or what is called the library approach. The form of activity in this literature study is by collecting data, reading, taking notes, and processing research materials. The research results found that students who experience subsequent acts of violence will tend to become perpetrators of acts of violence against other people. This phenomenon eventually becomes an unbroken chain, where each generation will treat the same thing in response to pressing situational conditions, so that this inherited pattern of behavior becomes a culture of violence. So, if the current parenting style still promotes violence, perhaps in 20-30 years our society will be even worse than what is being witnessed today.Â Spiritual Intelligence, Verbal Abuse Behavior